Factors Influencing Male Involvement in Antenatal Care in the Kassena Nankana Municipal in the Upper East Region, Ghana - Maxwell Tii Kumbeni; Florence Assibi Ziba; John Ndebugri Alem; Sylvia Apana Nborah (European Scientific Journal, ESJ, 2019)
Background: Globally, male involvement in antenatal care remains a challenge to the effective utilization of maternal health services. Male involvement is considered to be a useful tool that is capable of improving the health outcome of mothers and their children. However, matters relating to antenatal care have often been considered on a gender basis. Objective: The objective of this study was to assess the factors that influence male partner involvement in antenatal care services. Methods: A community-based crosssectional study was conducted among 420 men whose partners were pregnant or had delivered within twelve months preceding the study using multiple sampling procedures. Pearson Chi-Square and Fisher’s exact test were conducted to establish an association between dependent and independent variables after which multiple logistic regression was conducted. P-values of < 0.05 at 95% confidence interval were considered significant. Data were analyzed using STATA version 13.1. Results: The level of male involvement in antenatal care was high (67.2%). About 71.9% accompanied their partners to antenatal clinics at one point during the pregnancy period. Out of this, 45.7% of themdid so four or more times, 35.7% went two to three times, while 18.6% went only once. Factors such as staff attitude, time spent at the clinics, age, educational level, monthly income level, living with a partner during pregnancy, distance to the clinic, and community acceptability were all statistically significant to male involvement. Conclusion: The level of male involvement was high and considered above average. There is the need to develop interventions that will diffuse the existing socio-cultural perceptions and improve staff attitudes to achieve higher male involvement in antenatal care.